2023
DOI: 10.17305/bb.2022.8779
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis and coronavirus disease 2019 vaccination: A systematic review and meta-summary of cases

Abstract: Vaccination is significant to control, mitigate, and recover from the destructive effects of coronavirus disease 2019 (COVID-19). The incidence of myocarditis following COVID-19 vaccination has been increasing and growing public concern; however, little is known about it. This study aimed to systematically review myocarditis following COVID-19 vaccination. We included studies containing individual patient data of myocarditis following COVID-19 vaccination published between January 1, 2020 and September 7, 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 208 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the literature reports 218 cases of COVID-19 vaccine-associated myocarditis [ 114 ]. In a recent systematic review, 396 published cases of myocarditis were reported, predominantly in male patients, following the administration of the second dose of the mRNA vaccine [ 115 ]. Notably, they experienced chest pain as a symptom.…”
Section: Complications Of Covid-19mentioning
confidence: 99%
“…Additionally, the literature reports 218 cases of COVID-19 vaccine-associated myocarditis [ 114 ]. In a recent systematic review, 396 published cases of myocarditis were reported, predominantly in male patients, following the administration of the second dose of the mRNA vaccine [ 115 ]. Notably, they experienced chest pain as a symptom.…”
Section: Complications Of Covid-19mentioning
confidence: 99%
“…Recent reviews on the issue have highlighted that in patients developing myocarditis after the SARS-CoV-2 mRNA vaccine, comorbidities are present in less than half the number of cases. In most cases, the underlying disease is represented by an inflammatory or autoimmune disorder, while a previous history of myocarditis is present in only about 10% of cases [25]. However, some cardiovascular conditions, such as arterial hypertension, hypercholesterolemia, and aortic root dilation, may also act as contributing factors in the development of SARS-CoV-2-related myocarditis [26].…”
Section: Comorbidities and Clinical Presentationmentioning
confidence: 99%